2018
DOI: 10.1002/art.40539
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling and Clonal Tracking of Secreted Rheumatoid Factors in Primary Sjögren's Syndrome

Abstract: Cryoprecipitable RF clonotypes linked to vasculitis in primary SS have different molecular profiles than nonprecipitating RFs, suggesting different underlying mechanisms of production. The combined omics workflow presented herein provides molecular biomarkers for tracking and removal of pathogenic RF clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…In a recent proof-of-concept study, we have sequenced anti-H1 antibodies in archived sera from H1N1pdm09 influenza-vaccinated subjects and demonstrated convergent IgV subfamily landscapes of potential clinical utility [31]. In this regard, we have recently used MRM/MS with HCDR3 peptides to track serum rheumatoid factor (RF) clonotypes in patients with primary SS and mixed cryoglobulinaemia, and shown that pathogenic RF signatures appear years before clinical presentation [46]. In the longer term, temporal analysis of anti-dsDNA proteomes in larger patient populations, including newly diagnosed and asymptomatic subjects with anti-dsDNA, will be required to observe the dynamics of these secreted autoantibody repertoires.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent proof-of-concept study, we have sequenced anti-H1 antibodies in archived sera from H1N1pdm09 influenza-vaccinated subjects and demonstrated convergent IgV subfamily landscapes of potential clinical utility [31]. In this regard, we have recently used MRM/MS with HCDR3 peptides to track serum rheumatoid factor (RF) clonotypes in patients with primary SS and mixed cryoglobulinaemia, and shown that pathogenic RF signatures appear years before clinical presentation [46]. In the longer term, temporal analysis of anti-dsDNA proteomes in larger patient populations, including newly diagnosed and asymptomatic subjects with anti-dsDNA, will be required to observe the dynamics of these secreted autoantibody repertoires.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative MRM using the panel of surrogate anti-dsDNA clonotypical L-chain peptides identified herein will probably take the lead in these studies. In this regard, we have recently used MRM/MS with HCDR3 peptides to track serum rheumatoid factor (RF) clonotypes in patients with primary SS and mixed cryoglobulinaemia, and shown that pathogenic RF signatures appear years before clinical presentation [46]. Overall, this first comprehensive proteomic analysis of precipitating anti-dsDNA IgV peptide repertoires in lupus serum offers a fresh approach for characterizing and monitoring anti-dsDNA clonal populations with MS precision and accuracy, and for comparing their molecular signatures with other high-throughput 'omics' technologies [47].…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry (MS) may be used to molecularly type IgM RFs in cryoglobulins 2. Using an MS-based proteomic approach, we recently identified the immunoglobulin heavy chain variable region (IGHV) subfamilies and mutational profiles of cryoprecipitable IgM-RF in a group of primary Sjögren’s syndrome patients with mixed cryoglobulinemia, along with their clonotypic heavy chain complementarity-determining regions 3 (HCDR3) peptides 3. Subsequent quantitative proteomics, using the HCDR3 peptides as clonal barcodes, allowed identification and tracking of pathogenic RF clones in patients with type II mixed cryoglobulinemia before the onset of cutaneous vasculitis.…”
mentioning
confidence: 99%
“…To illustrate the resolving power of MS molecular profiling across different types of cryoglobulins, we have sequenced the heavy chains of routinely collected serum cryoglobulins4 from three patients with type I (monoclonal), type II (mixed monoclonal RF) and type III (mixed polyclonal RF) cryoglobulinemia. In brief, cryoglobulin heavy chains were fractionated and sequenced from sodium dodecyl sulfate-polyacrylamide gel electrophoresis in-gel digests as described 3. IGHV subfamilies and HCDR3 clonotypic peptides were subjected to analyses by a Q Exactive HF-X mass spectrometer.…”
mentioning
confidence: 99%
See 1 more Smart Citation